Diversity of Bryophyte in The Selarong Cave Area, Bantul, Yogyakarta - Zuchrotus Salamah; Hadi Sasongko; Efa Zulianti (Indonesian Journal of Biology Education, 2019)
The Selarong Cave area which is located in Bantul is a tourism site that has a humid environment condition due to the dense of big trees in these locations. There is also a waterfall. These conditions make it possible for bryophyte to grow surrounding the area. This research aims to identify the type of bryophyte grow in the Selarong Cave area, and know the characteristics. The method of this research is the exploration method which includes site investigation, identification, inventory, and descriptive analysis for both morphology and anatomy of the bryophyte. The finding of this research shows that there are 6 species of bryophyte which were found in the Selarong Cave area. They are Hyophila involuta (Hook.) Jaeg., Barbula consanguinea (Thw.&Mitt.) Jaeg., Bryum erytropus Fleisch., Weissia controversa Hedw., Preissia sp., and Vesicularia dubyana (C. Mull.) Broth.